PEMBENTUKAN KARAKTER RELIGIUS SISWA MELALUI PENDIDIKAN HUMANIS (Studi Kasus di SMK NU 2 Kedungpring Kabupaten Lamongan) - Yoyok Amirudin (Universitas Islam Lamongan, 2019)
This study discusses the formation of students' religious character through humanist education at SMK NU 2 Kedungpring, Lamongan Regency. This research is a case study research using a qualitative approach. Meanwhile, seen from the data presentation technique in this study using descriptive methods. The method used in this research with data collection techniques is the technique of observation, interviews, and documentation. While the data analysis technique used is descriptive qualitative analysis techniques. The results of this study indicate that the teacher acts as a trendsetter for the development of religious character through habituation, learning and interaction that emphasizes Islamic values. The factors that influence the formation of religious character through humanist education include the commitment of teachers who are not simultaneously in the development of religious character, besides that the lack of the number of religious teachers and the limited number of school facilities and infrastructure also affects the character building of humanist-religious students.